2022
DOI: 10.57187/smw.2022.40018
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative depression and anxiety as predictors of postoperative C-reactive protein levels in patients undergoing cardiac surgery: a prospective observational study

Abstract: AIM OF THE STUDY: In patients undergoing cardiac surgery, preoperative depressive and anxiety symptoms and increased postoperative C-reactive protein (CRP) levels have been associated with adverse outcomes. We tested the hypothesis that preoperative depressive and anxiety symptoms predict elevated in-hospital CRP levels after cardiac surgery. METHODS: The study participants were 96 consecutive patients (mean age [SD], 67.6 [10.3] years, 78.1% men) from a single cardiac surgery centre who underwent either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(54 reference statements)
0
0
0
Order By: Relevance
“…The high frequency of psychological disorders before surgery can be explained by the intensity of the preoperative symptoms, which, in some cases, can significantly impact daily functioning. Mood disorders are known to precede various surgical interventions, including hysterectomy [ 16 , 17 ]. Specifically, patients often express concerns about the possibility of pelvic neoplasia and attribute their preoperative symptoms to this potential risk.…”
Section: Discussionmentioning
confidence: 99%
“…The high frequency of psychological disorders before surgery can be explained by the intensity of the preoperative symptoms, which, in some cases, can significantly impact daily functioning. Mood disorders are known to precede various surgical interventions, including hysterectomy [ 16 , 17 ]. Specifically, patients often express concerns about the possibility of pelvic neoplasia and attribute their preoperative symptoms to this potential risk.…”
Section: Discussionmentioning
confidence: 99%
“…Since anxiety and depression are common among EBCR patients and significantly impact QoL and future cardiac events [ 20 22 ], another vital pillar of treatment during EBCR is psychological evaluation and support [ 7 ]. In fact, in addition to data from Cochrane reviews, two studies in which EBCR was supplemented by psychotherapy have recently been shown to reduce the HADS scores, improve QoL and adherence to EBCR, and reduced cardiovascular readmissions [ 9 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%